Suppression of interictal spikes during phasic rapid eye movement sleep: a quantitative stereo‐electroencephalography study. (12th April 2017) - Campana, C.; Zubler, F.; Gibbs, S.; de Carli, F.; Proserpio, P.; Rubino, A.; Cossu, M.; Tassi, L.; Schindler, K.; Nobili, L.
Summary: Tonic and phasic rapid eye movement (REM) sleep seem to represent two different brain states exerting different effects on epileptic activity. In particular, interictal spikes are suppressed strongly during phasic REM sleep. The reason for this effect is not understood completely. A different level of synchronization in phasic and tonic REM sleep has been postulated, yet never measured directly. Here we assessed the interictal spike rate across non‐REM (NREM) sleep, phasic and tonic REM sleep in nine patients affected by drug resistant focal epilepsy: five with type II focal cortical dysplasia and four with hippocampal sclerosis. Moreover, we applied different quantitative measures to evaluate the level of synchronization at the local and global scale during phasic and tonic REM sleep. We found a lower spike rate in phasic REM sleep, both within and outside the seizure onset zone. This effect seems to be independent from the histopathological substrate and from the brain region, where epileptic activity is produced (temporal versus extra‐temporal). A higher level of synchronization was observed during tonic REM sleep both on a large (global) and small (local) spatial scale. Phasic REM sleep appears to be an interesting model for understanding the mechanisms of suppression of epileptic activity.